2000
DOI: 10.1520/jfs14776j
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Factors in the Determination of Suicide in Self-Inflicted Gunshot Head Wounds

Abstract: Self-inflicted contact gunshot wounds to the head have usually been considered presumptive of suicide. This study evaluates whether sufficient psychological data are gathered in such cases to support a manner of death determination of suicide. We suggest that law enforcement agencies and coroner's departments do not fully explore the decedent's state of mind at the time of death. We studied the first 50 consecutive deaths in 1993 in a major metropolitan county due to self-inflicted gunshot wounds to the head. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…3 With respect to both types of injury, the limited opportunities for other means of self-harm in these settings might be important. 4 However, the same assumption cannot be made about intracranial self-stabbing, because our examination of the 47 published cases suggests that as many as one-third were not motivated by a desire to commit suicide. 29 Intracranial self-shooting carries a high risk of death and is usually assumed to be the result of a suicide attempt.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…3 With respect to both types of injury, the limited opportunities for other means of self-harm in these settings might be important. 4 However, the same assumption cannot be made about intracranial self-stabbing, because our examination of the 47 published cases suggests that as many as one-third were not motivated by a desire to commit suicide. 29 Intracranial self-shooting carries a high risk of death and is usually assumed to be the result of a suicide attempt.…”
Section: Discussionmentioning
confidence: 95%
“…The brain is almost completely protected by bone and can only be reached directly through soft tissue via the optic canal or orbital fissures. 4 In his book Bodies Under Siege; Self Mutilation in Culture and Psychiatry, Favazza described the 19th century case of a 25-year-old man with a severe psychotic illness who performed multiple self-mutilations, including self-emasculation, and who died after hammering a nail into his frontal lobe (p. 70). 2 In contrast to self-stabbing of the brain, self-inflicted gunshot injury to the brain is a recognized method of committing suicide and only a small proportion of people who do so are believed to be psychotic.…”
mentioning
confidence: 99%
“…Our findings concur with the other studies from India (Singh, 1984;Bhatia et al, 1998). However, western studies (Kreitman, 1988;Weinberger et al, 2000;Bennett and Collins, 2000;Cheng et al, 2000) highlight that a high incidence of suicide has been observed among unmarried people. The present study shows that there are probably different factors relating to marital or family life that are operating in the Indian culture.…”
Section: Discussionmentioning
confidence: 99%
“…The history of chronic debilitating illnesses, such as strokes and hypertension, combined with clinical depression, promote suicidal tendencies in some elders who do not have the resources to properly manage the adverse situation. Firearm injuries are the most common method of suicide in the United States, and the head is the most favored site of injury, however, despite the initial investigation report, the forehead flesh wound in this case made the true nature of the victim's COD less apparent until the autopsy was completed (17,(22)(23)(24)(25)(26)(27).…”
Section: Sudden Natural Death In Suicide Attempt_____________________mentioning
confidence: 95%